183. IMPACTS OF NEOADJUVANT CHEMORADIOTHERAPY ON THE IMMUNE LANDSCAPE OF ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (24th September 2022) - Wen, Jing; Fang, Shuogui; Hu, Yi; Xi, Mian; Weng, Zelin; Fu, Jianhua; Yang, Hong
Abstract: Neoadjuvant chemoradiation (neoCRT) followed by surgery is the most common approach for locally advanced resectable esophageal squamous cell carcinoma (ESCC) patients. Tumor microenvironment (TME) has been implicated in tumor response to treatment. Here, we aimed to investigate the impacts of neoCRT on the complex immune landscape in ESCC TME. Single-cell RNA sequencing (scRNA-seq) were conducted to examine the neoCRT-driven cellular and molecular dynamics in ESCC samples obtained before and after neoCRT. Consensus non-negative matrix factorization analysis was applied to decipher coherent gene expression programs of tumor cells. Activities of pathways and transcription factors of individual cells were analyzed by gene set variation and gene regulatory network analyses, respectively. Cell fate tracing was inferred by RNA velocity analysis. Multiplex fluorescent immunohistochemistry was performed to validate the changes of immune cells identified by scRNA-seq in another 25 pairs of pre- and post-neoCRT ESCC samples. Expression programs of cell cycle, adhesion, stress response, and epithelial differentiation in pre-treatment tumor cells related to neoCRT response. Infiltration of CD8+ T cells with exhausted cells dominant increased in both major and minor responders after neoCRT. Treg cell differentiation decreased after neoCRT in major responders but increased in minor ones. NeoCRT promoted the maturation of cDC1s but decreased the number of cDC2s. Expression of M2 macrophage markers increased after neoCRT. Immune-related pathways were enriched at higher levels in CD8+ T cells and macrophages of major responders as compared to minor responders before neoCRT, which was reversed after neoCRT. Our comprehensive picture of the neoCRT-related dynamic immune ecosystem provides deeper insights into immunological mechanisms associated with ESCC response to neoCRT, which may aid in future development of immune-strategies for improving ESCC treatment.